Relationship between robotic-assisted radical prostatectomy and retropubic radical prostatectomy in the learning curve of a single surgeon as a novice in radical prostatectomy: A retrospective cohort study. (September 2020) - Song, Wan; Lee, Sin Woo; Chung, Jae Hoon; Kang, Minyong; Sung, Hyun Hwan; Jeon, Hwang Gyun; Jeong, Byong Chang; Seo, Seong Il; Lee, Hyun Moo; Jeon, Seong Soo
Abstract: Objective: We compared the learning curve and pathologic and functional outcomes of retropubic radical prostatectomy (RRP) and robotic-assisted radical prostatectomy (RARP) performed during the same time period by a novice to identify how the two surgical types affect each other. Methods: We retrospectively reviewed 480 men who underwent RRP or RARP for prostate cancer between January 2008 and December 2012. Operation time, estimated blood loss (EBL), positive surgical margin (PSM) rate, urinary continence and potency recovery, and complications were compared. Scatter-graphs were drawn using locally weighted scatterplot smoothing (LOWESS). Results: Operation time reached the lowest point in the 90th case in RRP and the 200th case in RARP. EBL showed a similar pattern, reaching the lowest point in the 95th case in RRP and the 230th case in RARP. The lowest points for both operation time and EBL took about 3 years to reach for both surgical types. PSM rate was not significantly different ( P  = 0.807). No pads were required at 6 and 12 months in 55.6% and 66.9% of patients in RRP, respectively, but in 79.6% and 88.4% of patients in RARP. The potency recovery rates were 59.1% in RRP and 70.9% in RARP at 12 months. Conclusions: When RRP and RARP were begun contemporaneously by a novice, they showed similar learning curve patterns. The direct tactile feedback in RRP and the magnified field of view and detailed techniques in RARP help improve surgical skills complementarily to attain proficiency in both surgical types. Highlights: We compared the open and robotic radical prostatectomies performed during the same time period by a novice. The lowest points for both operation time and estimated blood loss took about 3 years to reach for both surgical types. The tactile feedback in open and the magnified view and detailed techniques in robotic surgery improve both surgical types.